2016
DOI: 10.1021/acs.langmuir.6b03467
|View full text |Cite
|
Sign up to set email alerts
|

Dip-and-Drag Lateral Force Spectroscopy for Measuring Adhesive Forces between Nanofibers

Abstract: Adhesive interactions between nano-fibers strongly influence the mechanical behavior of soft materials comprised of fibrous networks. We use atomic force microscopy (AFM) in lateral force mode to drag a cantilever tip through fibrous networks, and use the measured lateral force response to determine the adhesive forces between fibers of the order of 100 nm diameter. The peaks in lateral force curves are directly related to the detachment energy between two fibers; the data is analyzed using the Jarzynski equal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…The recorded lateral force-distance curves, an example of which is shown in Figure 2B, feature force peaks that consistently rise above the baseline. Following the methods established in our previous work (Dolan et al, 2016), the observed sharp increase…”
Section: Microstructure and Dnd-lfs On Bc Hydrogelsmentioning
confidence: 75%
See 4 more Smart Citations
“…The recorded lateral force-distance curves, an example of which is shown in Figure 2B, feature force peaks that consistently rise above the baseline. Following the methods established in our previous work (Dolan et al, 2016), the observed sharp increase…”
Section: Microstructure and Dnd-lfs On Bc Hydrogelsmentioning
confidence: 75%
“…In this work we aim to probe the interactive forces between nanoscale cellulose fibres and explore the effect of non-cellulosic components (arabinoxylan and xyloglucan) on inter-fibre adhesion (Dolan, 2017). To enable such nano-scale characterisation, we adapted and further advanced our recently developed dip-and-drag lateral force spectroscopy (DnD-LFS) technique (Dolan et al, 2016), which uses an AFM cantilever tip to pull fibres out of a network and measure forces associated with detachment events at fibre contacts. Building on previous developments (Lopez-Sanchez, Cersosimo, Wang, Flanagan, Stokes & Gidley, 2015; Martinez-Sanz, Whitney, Gothard, Mitchell & Gidley, 1999), BC networks are used as a model system and are self-assembled to give a random distribution of fibre orientations and contact configurations.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 3 more Smart Citations